High-temperature start-stop battery cathode lead paste for vehicle and preparation method of high-temperature start-stop battery cathode lead paste
By adding a variety of additives to the lead paste and optimizing the preparation process, the shortcomings of traditional lead-acid battery negative electrode materials in terms of conductivity, structural stability and cycle life are solved, and high-performance automotive high-temperature start-stop battery negative lead paste is achieved, improving the comprehensive performance and application potential of the battery.
Patent Information
- Application Number
- CN202510398490.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-04-01
- Publication Date
- 2025-05-02
- Estimated Expiration
- 2045-04-01
AI Technical Summary
Traditional lead-acid battery negative electrode materials have shortcomings in terms of conductivity, structural stability and cycle life, especially in high-power discharge and fast charging and discharge application scenarios, which limits its application potential in emerging fields such as electric vehicles.
By optimizing the composition and preparation process of lead paste, a variety of additives such as polyester short fiber, nano-grade barium sulfate, nano-grade sodium sulfate, high-temperature resistant additives and carbon materials are added to form a high-performance automotive high-temperature start-stop battery negative lead paste.
It significantly improves the battery's conductivity, cycle life, rate performance and energy density, enhances structural stability, and meets the needs of high-performance application scenarios.
Smart Images

Figure SMS_1 
Figure SMS_2
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of battery materials, and in particular to a negative electrode lead paste for a high-temperature start-stop battery for a vehicle and a preparation method thereof. Background Art
[0002] Lead-acid batteries have an irreplaceable position in many fields such as automobile starting, backup power systems and new energy storage solutions due to their low cost, good stability and reliability. However, with the advancement of technology and changes in market demand, the performance bottleneck of traditional lead-acid batteries has gradually emerged, especially in the preparation and optimization of negative electrode materials, which face many challenges.
[0003] The negative electrode of a traditional lead-acid battery usually uses lead paste prepared by directly mixing lead powder and dilute sulfuric acid as the active material. Although this preparation method is simple and direct, it has obvious performance limitations. First, the insufficient conductivity of the lead paste is a key issue. Due to the lack of effective conductive additives, the electron conduction capacity inside the lead paste is limited, resulting in low reaction efficiency of the active material, which in turn affects the discharge capacity and power output of the battery. This defect is particularly prominent in application scenarios that require high-power discharge or fast charging and discharging, limiting the application potential of lead-acid batteries in emerging fields such as electric vehicles and smart grids.
[0004] Secondly, the structural stability of traditional negative lead paste is poor, and the paste is prone to expansion, cracking, or even falling off during the cycle. This not only leads to a significant reduction in the effective utilization rate of active materials, but also accelerates the decline of battery performance and shortens the cycle life. Especially after deep discharge or high current charge and discharge cycles, the structural damage of the negative lead paste is more serious, and the battery performance declines more significantly, making it difficult to meet the requirements of long life and high reliability.
[0005] In response to the above problems, researchers are actively exploring new ways to improve the negative electrode materials of lead-acid batteries. Among them, adding conductive additives to lead paste to enhance its conductivity and structural stability has become one of the research hotspots. Carbon materials, such as carbon black, graphite, carbon nanotubes, etc., are considered ideal choices for improving the conductivity of lead paste due to their excellent conductive properties and good chemical stability. These carbon materials can form a conductive network, increase the transmission rate of electrons in the lead paste, and thus improve the reaction efficiency of active substances. However, the addition of carbon materials is not the more the better. Factors such as its particle size, distribution uniformity, and interaction with lead powder will affect the final effect. Therefore, how to optimize the addition strategy of carbon materials and achieve their uniform dispersion in the lead paste has become a technical problem that needs to be solved urgently.
[0006] In addition, in order to improve the mechanical strength and structural stability of the lead paste, researchers have also tried to introduce organic additives and inorganic fillers. For example, ultrafine barium sulfate as a filler can increase the density and hardness of the lead paste and reduce the deformation and shedding of the paste during the cycle; organic additives such as polyester staple fibers can enhance the toughness of the lead paste and improve its ability to withstand cyclic stress. The rational use of these additives can help improve the overall performance of the negative electrode lead paste and extend the service life of the battery.
[0007] In summary, in the face of the shortcomings of traditional lead-acid battery negative electrode materials in conductivity, structural stability and cycle life, the development of an improved negative electrode lead paste containing a variety of additives is of great significance for improving the comprehensive performance of lead-acid batteries and broadening their application areas. Summary of the invention
[0008] In response to the above technical problems, the present method optimizes the lead paste composition and preparation process to further improve the electrochemical performance, cycle life and energy density of lead-acid batteries, thereby meeting the needs of high-performance application scenarios.
[0009] To achieve the above object, the present invention provides the following technical solutions: A negative electrode lead paste for a high-temperature start-stop battery for a vehicle comprises lead powder, sulfuric acid solution, water and an additive. The additive comprises the following raw materials in parts by weight based on 100 parts by weight of the lead powder: 0.5-1 part of polyester staple fiber, 0.5-2 parts of nano-grade barium sulfate, 0.2-1 parts of nano-grade sodium sulfate, 0.1-1 parts of high temperature resistant additives, and 0.2-1 parts of carbon material additives; The high temperature resistant additive is obtained by the reaction of polyaniline with 9H-carbazole-3-sulfonyl chloride to generate sulfonamidation, and coordination with indium acetate.
[0010] Preferably, the carbon material additive is selected from one or a combination of carbon black, carbon nanotubes, graphene, acetylene black, and carbon fiber.
[0011] Specifically, the high temperature resistant additive is modified polyaniline, and the preparation method thereof is as follows: 100-120 parts of polyaniline are dispersed in 1000-1200 parts of 1,2-dichloroethane, 14-20 parts of 9H-carbazole-3-sulfonyl chloride, 0.03-0.3 parts of indium acetate and 3-6 parts of aluminum chloride are added, and the mixture is heated to 70-80° C., reacted for 2-4 hours, 1,2-dichloroethane is removed by distillation, and dried to obtain the high temperature resistant additive.
[0012] Beneficial effects of the above-mentioned high temperature resistant additives: 1) Improve high temperature resistance: Carbazole ring has good thermal stability, and introducing it into polyaniline can significantly improve the high temperature resistance of the material. This is crucial for the negative electrode lead paste of high temperature start-stop batteries for vehicles, because such batteries need to be started and stopped frequently in high temperature environments.
[0013] 2) Enhanced electrochemical performance: The formation of organic indium complexes helps to improve the electrochemical properties of materials, such as increasing conductivity, reducing resistance, etc. This has a positive impact on the charge and discharge performance and cycle life of the battery.
[0014] 3) Improve structural stability: The introduction of carbazole rings can also increase the intermolecular forces of the material, thereby improving its structural stability. This is of great significance for maintaining the performance of the battery during long-term use.
[0015] Specifically, based on 100 parts by weight of the lead powder, the sulfuric acid solution comprises 10-20 parts, with a volume concentration of 5%-10%, and water comprises 30-50 parts, wherein the oxidation degree of the lead powder can be 60%-80%.
[0016] The present invention provides a method for preparing the negative electrode lead paste of a high-temperature start-stop battery for a vehicle, comprising the following steps: Step 1: Add polyester staple fibers, nano-grade sodium sulfate and nano-grade barium sulfate into water, wet-mix and mix evenly to obtain a mixed solution; meanwhile, dry-mix a high temperature resistant additive, a carbon material additive and lead powder to obtain a mixed powder; Step 2: Evenly mix the mixed solution and the mixed powder, then keep the mixture in a mixed state, add sulfuric acid solution, and obtain the negative electrode lead paste of the high-temperature start-stop battery for a vehicle.
[0017] Preferably, in step 1, the wet mixing is performed by stirring, the stirring speed is 300-600 rpm, and the stirring time is 10-20 minutes; The dry mixing method is ball milling, the rotation speed of the ball mill is 100-300 rpm, the ball milling time is 10-25 minutes, and the ball-to-material ratio is 8-12:1.
[0018] Preferably, in step 2, during the process of adding sulfuric acid solution to the paste, the temperature is controlled at 50-70°C.
[0019] Preferably, in step 2, the apparent density of the prepared negative electrode lead paste is 3.5-4.5 g / cm 3 , needle penetration is 15-25mm.
[0020] Preferably, in step 2, after adding the sulfuric acid solution, the paste is mixed and the lead paste is cured and dried. The curing temperature is 35-45° C., the humidity during the curing process is controlled at 75%-95%, and the curing time is 24-36 hours.
[0021] Preferably, the drying temperature is 50-65° C. and the drying time is 18-24 hours.
[0022] Compared with the prior art solutions, the present invention has the following beneficial effects: The acylation reaction of polyaniline with 9H-carbazole-3-sulfonyl chloride and indium acetate in the present invention not only successfully introduced carbazole rings and organic indium complexes, but also significantly improved the high temperature resistance, conductivity (internal resistance reduced by half), cycle life (up to about 61%), rate performance (up to 11%), energy density and structural stability of the material. These technical effects are of great significance for the application of negative electrode lead paste for high temperature start-stop batteries for vehicles. DETAILED DESCRIPTION
[0023] Example 1
[0024] The preparation method of the high temperature resistant additive used in this embodiment is: 100 g of polyaniline was dispersed in 1000 g of 1,2-dichloroethane, 14 g of 9H-carbazole-3-sulfonyl chloride, 0.03 g of indium acetate and 3 g of aluminum chloride were added, and the mixture was heated to 70° C. and reacted for 4 h. 1,2-dichloroethane was removed by distillation, and the mixture was dried to obtain a high temperature resistant additive.
[0025] A method for preparing a negative electrode lead paste for a high-temperature start-stop battery for a vehicle comprises the following steps: Step 1: Add 0.5g polyester staple fiber, 0.5g nano-barium sulfate and 0.2g nano-sodium sulfate to 30g deionized water, stir for 10 minutes at a stirring speed of 300rpm to obtain a mixed solution; at the same time, put 0.1g high temperature resistant additive, 0.2g carbon black and 100g lead powder (oxidation degree of 60%) into a ball mill, use a ball mill to mix, the ball mill speed is 100rpm, the ball milling time is 10 minutes, and the ball-to-material ratio is 8:1 to obtain a mixed powder; Step 2: Mix the above mixed solution and mixed powder, stir continuously for 10 minutes during the mixing process, then slowly pour 10g of dilute sulfuric acid (volume concentration of 5%) while stirring, continue stirring for 10 minutes, use deionized water to adjust the apparent density of the lead paste to 3.5 g / cm³ and the needle penetration to 15 mm, complete the paste, control the temperature of the paste process at 50°C, then cure the lead paste at a curing temperature of 35°C and a humidity of 75% during the curing process for 24 hours; then dry at a drying temperature of 50°C for 24 hours to obtain the negative electrode lead paste described in this method.
[0026] Example 2
[0027] The preparation method of the high temperature resistant additive used in this embodiment is: 110 g of polyaniline was dispersed in 1100 g of 1,2-dichloroethane, 16 g of 9H-carbazole-3-sulfonyl chloride, 0.1 g of indium acetate and 4 g of aluminum chloride were added, and the mixture was heated to 75° C. and reacted for 3 h. 1,2-dichloroethane was removed by distillation, and the mixture was dried to obtain a high temperature resistant additive.
[0028] A method for preparing a negative electrode lead paste for a high-temperature start-stop battery for a vehicle comprises the following steps: Step 1: Add 0.75g polyester staple fiber, 1g nano-barium sulfate and 0.5g nano-sodium sulfate to 40g deionized water, and stir for 15 minutes at a stirring speed of 400rpm to obtain a mixed solution; at the same time, put 0.4g high temperature resistant additive, 0.8g carbon nanotubes and 100g lead powder (oxidation degree of 70%) into a ball mill, and use a ball mill to mix them, the ball milling speed is 200rpm, the ball milling time is 15 minutes, and the ball-to-material ratio is 10:1 to obtain a mixed powder; Step 2: Mix the above mixed solution and mixed powder, stir continuously for 15 minutes during the mixing process, then slowly pour in 15g of dilute sulfuric acid (volume concentration of 7%) while stirring, continue stirring for 12 minutes, use deionized water to adjust the apparent density of the lead paste to 4 g / cm³ and the needle penetration to 20 mm, complete the paste, control the temperature of the paste process at 60°C, then cure the lead paste at a curing temperature of 40°C and a humidity of 85% during the curing process for 28 hours; then dry at a drying temperature of 55°C for 22 hours to obtain the negative electrode lead paste described in this method.
[0029] Example 3
[0030] The preparation method of the high temperature resistant additive used in this embodiment is: 110 g of polyaniline was dispersed in 1100 g of 1,2-dichloroethane, 18 g of 9H-carbazole-3-sulfonyl chloride, 0.2 g of indium acetate and 5 g of aluminum chloride were added, and the mixture was heated to 75° C. and reacted for 3 h. 1,2-dichloroethane was removed by distillation and dried to obtain a high temperature resistant additive.
[0031] A method for preparing a negative electrode lead paste for a high-temperature start-stop battery for a vehicle comprises the following steps: Step 1: Add 0.8g polyester staple fiber, 1.5g nano-barium sulfate and 0.8g nano-sodium sulfate to 40g deionized water, stir for 15 minutes at a stirring speed of 500rpm to obtain a mixed solution; at the same time, put 0.8g high temperature resistant additive, 0.8g graphene and 100g lead powder (oxidation degree of 70%) into a ball mill, use a ball mill to mix, the ball mill speed is 200rpm, the ball milling time is 20 minutes, and the ball-to-material ratio is 10:1 to obtain a mixed powder; Step 2: Mix the above mixed solution and mixed powder, stir continuously for 15 minutes during the mixing process, then slowly pour 15g of dilute sulfuric acid (volume concentration of 8%) while stirring, continue stirring for 13 minutes, use deionized water to adjust the apparent density of the lead paste to 4 g / cm³ and the needle penetration to 20 mm, complete the paste, control the temperature of the paste process at 60°C, then cure the lead paste at a curing temperature of 40°C and a humidity of 85% during the curing process for 28 hours; then dry at a drying temperature of 60°C for 20 hours to obtain the negative electrode lead paste described in this method.
[0032] Example 4
[0033] The preparation method of the high temperature resistant additive used in this embodiment is: 120 g of polyaniline was dispersed in 1200 g of 1,2-dichloroethane, 20 g of 9H-carbazole-3-sulfonyl chloride, 0.3 g of indium acetate and 6 g of aluminum chloride were added, and the mixture was heated to 80° C. and reacted for 2 h. 1,2-dichloroethane was removed by distillation, and the mixture was dried to obtain a high temperature resistant additive.
[0034] A method for preparing a negative electrode lead paste for a high-temperature start-stop battery for a vehicle comprises the following steps: Step 1: Add 1g of polyester staple fiber, 2g of nano-barium sulfate and 1g of nano-sodium sulfate to 50g of deionized water, and stir for 20 minutes at a stirring speed of 600rpm to obtain a mixed solution; at the same time, put 1g of high temperature resistant additive, 1g of acetylene carbon black and 100g of lead powder (oxidation degree of 80%) into a ball mill, and use a ball mill to mix them, the ball milling speed is 300rpm, the ball milling time is 25 minutes, and the ball-to-material ratio is 12:1 to obtain a mixed powder; Step 2: Mix the above mixed solution and mixed powder, stir continuously for 20 minutes during the mixing process, then slowly pour in 20g of dilute sulfuric acid (volume concentration of 10%) while stirring, continue stirring for 15 minutes, use deionized water to adjust the apparent density of the lead paste to 4.5 g / cm³ and the needle penetration to 25 mm, complete the paste, control the temperature of the paste process to 70°C, then cure the lead paste at a curing temperature of 45°C and a humidity of 95% during the curing process for 36 hours; then dry at a drying temperature of 65°C for 18 hours to obtain the negative electrode lead paste described in this method.
[0035] Comparative Example 1
[0036] A method for preparing a negative electrode lead paste for a high-temperature start-stop battery for a vehicle comprises the following steps: Step 1: Add 0.5g polyester staple fiber, 0.5g nano-barium sulfate and 0.2g nano-sodium sulfate into 30g deionized water, stir for 10 minutes at a stirring speed of 300rpm to obtain a mixed solution; at the same time, put 0.2g carbon black and 100g lead powder (oxidation degree of 60%) into a ball mill, use a ball mill to mix, the ball mill speed is 100rpm, the ball milling time is 10 minutes, and the ball-to-material ratio is 8:1 to obtain a mixed powder; Step 2: Mix the above mixed solution and mixed powder, stir continuously for 10 minutes during the mixing process, then slowly pour 10g of dilute sulfuric acid (volume concentration of 5%) while stirring, continue stirring for 10 minutes, use deionized water to adjust the apparent density of the lead paste to 3.5 g / cm³ and the needle penetration to 15 mm, complete the paste, control the temperature of the paste process at 50°C, then cure the lead paste at a curing temperature of 35°C and a humidity of 75% during the curing process for 24 hours; then dry at a drying temperature of 50°C for 24 hours to obtain the negative electrode lead paste described in this method.
[0037] Comparative Example 2
[0038] The additive used in this comparative example is modified polyaniline, and its preparation method is: 100 g of polyaniline was dispersed in 1000 g of 1,2-dichloroethane, 14 g of 9H-carbazole-3-sulfonyl chloride and 3 g of aluminum chloride were added, and the mixture was heated to 70° C. and reacted for 4 h. 1,2-dichloroethane was removed by distillation, and the mixture was dried to obtain an additive.
[0039] A method for preparing a negative electrode lead paste for a high-temperature start-stop battery for a vehicle comprises the following steps: Step 1: Add 0.5g polyester staple fiber, 0.5g nano-barium sulfate and 0.2g nano-sodium sulfate to 30g deionized water, stir for 10 minutes at a stirring speed of 300rpm to obtain a mixed solution; at the same time, put 0.1g additive, 0.2g carbon black and 100g lead powder (oxidation degree of 60%) into a ball mill, use a ball mill to mix, the ball mill speed is 100rpm, the ball milling time is 10 minutes, and the ball-to-material ratio is 8:1 to obtain a mixed powder; Step 2: Mix the above mixed solution and mixed powder, stir continuously for 10 minutes during the mixing process, then slowly pour 10g of dilute sulfuric acid (volume concentration of 5%) while stirring, continue stirring for 10 minutes, use deionized water to adjust the apparent density of the lead paste to 3.5 g / cm³ and the needle penetration to 15 mm, complete the paste, control the temperature of the paste process at 50°C, then cure the lead paste at a curing temperature of 35°C and a humidity of 75% during the curing process for 24 hours; then dry at a drying temperature of 50°C for 24 hours to obtain the negative electrode lead paste described in this method.
[0040] Comparative Example 3 The additive used in this comparative example is modified polyaniline, and its preparation method is: 100 g of polyaniline was dispersed in 1000 g of 1,2-dichloroethane, 0.03 g of indium acetate and 3 g of aluminum chloride were added, and the mixture was heated to 70° C. and reacted for 4 hours. 1,2-dichloroethane was removed by distillation, and the mixture was dried to obtain an additive.
[0041] A method for preparing a negative electrode lead paste for a high-temperature start-stop battery for a vehicle comprises the following steps: Step 1: Add 0.5g polyester staple fiber, 0.5g nano-barium sulfate and 0.2g nano-sodium sulfate to 30g deionized water, stir for 10 minutes at a stirring speed of 300rpm to obtain a mixed solution; at the same time, put 0.1g additive, 0.2g carbon black and 100g lead powder (oxidation degree of 60%) into a ball mill, use a ball mill to mix, the ball mill speed is 100rpm, the ball milling time is 10 minutes, and the ball-to-material ratio is 8:1 to obtain a mixed powder; Step 2: Mix the above mixed solution and mixed powder, stir continuously for 10 minutes during the mixing process, then slowly pour 10g of dilute sulfuric acid (volume concentration of 5%) while stirring, continue stirring for 10 minutes, use deionized water to adjust the apparent density of the lead paste to 3.5 g / cm³ and the needle penetration to 15 mm, complete the paste, control the temperature of the paste process at 50°C, then cure the lead paste at a curing temperature of 35°C and a humidity of 75% during the curing process for 24 hours; then dry at a drying temperature of 50°C for 24 hours to obtain the negative electrode lead paste described in this method.
[0042] Test Example 1
[0043] 1. Test method (applicable to batteries for two-wheeled and three-wheeled vehicles): 1. Conductivity test: Use electrochemical impedance spectroscopy (EIS) to test the internal resistance of the electrode, with a frequency range of 10 -2 Hz to 10 6 Hz, measure the minimum value of AC impedance.
[0044] 2. Cycle life test: At 25°C, the lead-acid battery is subjected to cycle charge and discharge test according to the International Battery Association (IEC) standard. Cycle conditions: constant current charging current 0.2C, constant current discharge to 1.8 V, and the number of cycles is counted.
[0045] 3. Energy density test: Under 0.1C rate conditions, measure the discharge capacity of the battery and calculate the battery mass energy density (Wh / kg).
[0046] 4. Rate performance test: At a discharge rate of 0.5C, measure the discharge capacity of the battery and calculate the rate retention rate.
[0047] 2. Test method (applicable to automotive batteries) Fully charged batteries are tested in a 75℃±3℃ water bath according to the following test cycle: a) Discharge at 25A for 18s; b) Constant voltage 14.2V, current limit 25A charging for 30min; c) Discharge at 3A for 15min; d) Constant voltage 14.2V, current limit 25A charging for 30min; e) Discharge at 25A for 18s; f) Constant voltage 14.2V, current limit 25A charging for 30min; g) Discharge at 3A for 15min; h) Constant voltage 14.2V, current limit 25A charging for 30min; i) Discharge at 3A for 15min; j) Constant voltage 14.2V, current limit 25A charging 29min24s; The battery was cycled 6 times according to steps a)-j), and each cycle took 3.25 h; k) After the 6 cycles, discharge at 10A for 15min, and then charge at a constant voltage of 14.2V and a current limit of 25A for 255min; l) Repeat a)-k) 4 more times; m) Repeat a)-j) 4 times; n) Discharge at 10A for 15min; o) Constant voltage 14.2V, current limit 25A charging for 120min; The above test consists of 34 cycles.
[0048] p) The battery is placed in an open circuit at an ambient temperature of 75℃±2℃ for 28h~33h; q) Then discharge with 200A current for 10s. The voltage is required to be greater than 7.2V in 10s, otherwise the test is terminated; r) a)-f) is a unit; s) The test is terminated if one or more of the following occurs: - At the end of any charging step, the current is higher than 15A; ——At the end of any discharge step, the voltage is lower than 7.2V; ——When in static state, the voltage is lower than 12V.
[0049] The test results for batteries for two-wheeled and three-wheeled vehicles are shown in Table 1.
[0050] Table 1 Test results
[0051] The 75°C high temperature test results for automotive batteries are shown in Table 2.
[0052] Table 2 Test results
[0053] The above test results show that the negative electrode lead paste prepared by the present invention has significantly improved conductivity, cycle life, rate performance, energy density and high temperature resistance compared with the comparative sample, verifying the effectiveness and superiority of the technical solution of the present invention.
Claims
1. A negative electrode lead paste for a high temperature start-stop battery for a vehicle, comprising lead powder, sulfuric acid solution, water and additives, characterized in that: Based on 100 parts by weight of lead powder, the additive comprises the following raw materials in parts by weight: 0.5-1 part of polyester staple fiber, 0.5-2 parts of nano-grade barium sulfate, 0.2-1 parts of nano-grade sodium sulfate, 0.1-1 parts of high temperature resistant additives, and 0.2-1 parts of carbon material additives; The high temperature resistant additive is obtained by the reaction of polyaniline with 9H-carbazole-3-sulfonyl chloride to generate sulfonamidation, and coordination with indium acetate.
2. The negative electrode lead paste for high temperature start-stop battery for vehicle according to claim 1, characterized in that: The carbon material additive is selected from one or a combination of carbon black, carbon nanotubes, graphene, acetylene black, and carbon fiber.
3. The negative electrode lead paste for high temperature start-stop battery for vehicle according to claim 1, characterized in that: The high temperature resistant additive is modified polyaniline, and its preparation method is as follows: 100-120 parts of polyaniline are dispersed in 1000-1200 parts of 1,2-dichloroethane, 14-20 parts of 9H-carbazole-3-sulfonyl chloride, 0.03-0.3 parts of indium acetate and 3-6 parts of aluminum chloride are added, and the mixture is heated to 70-80° C., reacted for 2-4 hours, 1,2-dichloroethane is removed by distillation, and dried to obtain the high temperature resistant additive.
4. The negative electrode lead paste for high temperature start-stop battery for vehicle according to claim 1, characterized in that: Based on 100 parts by weight of the lead powder, the sulfuric acid solution comprises 10-20 parts with a volume ratio concentration of 5%-10%; and water comprises 30-50 parts.
5. The method for preparing the negative electrode lead paste of a high temperature start-stop battery for a vehicle according to any one of claims 1 to 4, characterized in that: The following steps are involved: Step 1: Add polyester staple fibers, nano-barium sulfate and nano-sodium sulfate into water, wet mix and mix evenly to obtain a mixed solution; at the same time, dry mix a high temperature resistant additive, a carbon material additive and lead powder to obtain a mixed powder; Step 2: Evenly mix the mixed solution and the mixed powder, then keep the mixture in a mixed state, add sulfuric acid solution, and obtain the negative electrode lead paste of the high-temperature start-stop battery for a vehicle.
6. The method for preparing the negative electrode lead paste of a high temperature start-stop battery for a vehicle according to claim 5, characterized in that: In step 1, the wet mixing is carried out by stirring, the stirring speed is 300-600 rpm, and the stirring time is 10-20 minutes; The dry mixing method is ball milling, the rotation speed of the ball mill is 100-300 rpm, the ball milling time is 10-25 minutes, and the ball-to-material ratio is 8-12:
1.
7. The method for preparing the negative electrode lead paste of a high temperature start-stop battery for a vehicle according to claim 5, characterized in that: In step 2, during the process of adding sulfuric acid solution to the paste, the temperature is controlled at 50-70°C.
8. The method for preparing the negative electrode lead paste of a high temperature start-stop battery for a vehicle according to claim 5, characterized in that: In step 2, the apparent density of the prepared negative electrode lead paste is 3.5-4.5 g / cm 3 , needle penetration is 15-25 mm.
9. The method for preparing the negative electrode lead paste of a high temperature start-stop battery for a vehicle according to claim 5, characterized in that: In step 2, after adding the sulfuric acid solution, the paste is mixed and the lead paste is cured and dried. The curing temperature is 35-45° C., the humidity is controlled at 75%-95% during the curing process, and the curing time is 24-36 hours.
10. The method for preparing the negative electrode lead paste for a high temperature start-stop battery for a vehicle according to claim 9, characterized in that: The drying temperature is 50-65°C and the drying time is 18-24 hours.
Citation Information
Patent Citations
Lead-acid battery cathode lead paste containing polyaniline
CN103022503A
Image forming apparatus and process cartridge
CN104007647A
High-temperature heavy-load negative lead paste for start-stop battery and preparation method of negative lead paste
CN105702953A
A negative plate lead paste used for starting and stopping lead-carbon super batteries with high performance and a preparation method thereof
CN109103426A
Lead paste formula of positive plate of start-stop storage battery, positive plate and preparation method thereof
CN112490437A